The Beauty of Asymmetric Membranes: Reconstitution of the Outer Membrane of Gram-Negative Bacteria - Paulowski, Laura; Donoghue, Annemarie; Nehls, Christian; Groth, Sabrina; Koistinen, Max; Hagge, Sven O.; Böhling, Arne; Winterhalter, Mathias; Gutsmann, Thomas (Frontiers in Cell and Developmental Biology, 2020)
The architecture of the lipid matrix of the outer membrane of Gram-negative bacteria is extremely asymmetric: Whereas the inner leaflet is composed of a phospholipid mixture, the outer leaflet is built up by glycolipids. For most Gram-negative species, these glycolipids are lipopolysaccharides (LPS), for a few species, however, glycosphingolipids. We demonstrate experimental approaches for the reconstitution of these asymmetric membranes as (i) solid supported membranes prepared by the Langmuir-Blodgett technique, (ii) planar lipid bilayers prepared by the Montal-Mueller technique, and (iii) giant unilamellar vesicles (GUVs) prepared by the phase transfer method. The asymmetric GUVs (aGUVs) composed of LPS on one leaflet are shown for the first time. They are characterized with respect to their phase behavior, flip-flop of lipids and their usability to investigate the interaction with membrane active peptides or proteins. For the antimicrobial peptide LL-32 and for the bacterial porin OmpF the specificity of the interaction with asymmetric membranes is shown. The three reconstitution systems are compared with respect to their usability to investigate domain formation and interactions with peptides and proteins.